WARISAN ANDALUSIA: JEJAK INTELEKTUAL ISLAM DALAM SEJARAH SPANYOL - Marwah Maulana Sidik; Akbar Al Firdaus; M.Tajudin Zuhri; Nenden Munawaroh; Masripah (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to examine the development of Islamic civilization and thought in Spain, particularly during the golden era of Al-Andalus (711–1492 CE). Employing a literature review approach, this research gathers and analyzes various historical and scholarly sources that discuss the contributions of Muslims in science, philosophy, art, and culture. The findings reveal that Al-Andalus served as an intellectual hub of the Islamic world, acting as a bridge of knowledge between the East and the West. Figures such as Ibn Rushd and Ibn Arabi demonstrated remarkable achievements in philosophy and mysticism, with their ideas also influencing intellectual developments in Europe. Furthermore, the harmonious interaction among Muslims, Christians, and Jews in Al-Andalus fostered a climate of tolerance that invigorated the exchange of knowledge and culture. This research underscores that the legacy of Islamic civilization in Spain holds significance not only for Islamic history but also for the advancement of global civilization.